THE EFFECTIVE OF PRE-QUESTION TECHNIQUES ON STUDENT’S READING NARRATIVE TEXT AT SMA N 1 PEGAJAHAN: EFEKTIFITAS TEKNIK PRE-QUESTION PADA PEMBACAAN TEKS NARASI SISWA DI SMA N 1 PEGAJAHAN - Puspita Sari, Bella (LPPM UPMI, 2024)
This study investigates the impact of pre-question techniques on students’ reading comprehension achievment at SMA N 1 Pegajahan. Pre-question techniques involve asking questions before reading to activate prior knowledge and set reading purposes. This quasi-experimental method is applied in this research with pre test-post test. This research has been executed at SMA N 1 Pegajahan. The researcher took X-1 class control class and X-2 class experimental class. The experimental research with one group pre-test and post-test design was applied in this research. In collecting the data, pre-test, treatments, and post-test were administered. Then, the t-test was employed to reach the significant value. The result of the research proves that pre-questioning technique gives positive effect on students’ reading comprehension achievement. It can be seen from the mean score of the students in pre-test and post-test which computated by SPSS 16.00 . In pre-test, the mean score is 68.46 and it increases 76.86 in post-test. It means that there is an increase of 8.40 points. The result of t-test shows that t-ratio is higher than t-table (13.146 > 2.045) with the level of significant is p < 0.05 and significant two tail is p=0.000. It can be said that pre- questioning technique gives the positive impact because it can increase students’ reading comprehension achievement.